2010
DOI: 10.1210/jc.2009-2040
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Factor 1 Overexpression and Gene Amplification Are More Frequent in Adrenocortical Tumors from Children than from Adults

Abstract: We demonstrated a higher frequency of SF-1 overexpression and gene amplification in pediatric than in adult adrenocortical tumors, suggesting an important role of SF-1 in pediatric adrenocortical tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 23 publications
2
60
0
11
Order By: Relevance
“…Namely, those animals lacked steroidogenic tissues, such as adrenal glands and gonads [9][10][11][12] . By contrast, the overexpression of Ad4BP/SF-1 induced enlargement/ectopic formation and tumorigenesis of the adrenal cortex [13][14][15][16] . Taken together, these studies strongly suggested that Ad4BP/SF-1 is involved in the regulation of cellular proliferation and maintenance.…”
mentioning
confidence: 88%
“…Namely, those animals lacked steroidogenic tissues, such as adrenal glands and gonads [9][10][11][12] . By contrast, the overexpression of Ad4BP/SF-1 induced enlargement/ectopic formation and tumorigenesis of the adrenal cortex [13][14][15][16] . Taken together, these studies strongly suggested that Ad4BP/SF-1 is involved in the regulation of cellular proliferation and maintenance.…”
mentioning
confidence: 88%
“…Apart from transcriptome analyses, one of the most common methods to screen a large number of samples is tissue microarray: it has been widely used for immunohistochemistry studies on adrenocortical tumours [21,34,51,52,67,69,80,168].…”
Section: Molecular Research Methodsmentioning
confidence: 99%
“…some gain or amplification at 9q33 [65][66][67]. SF-1 also shows prognostic information: higher expression correlates with more advanced tumour stage, poorer clinical outcome, and shorter overall survival [68,69].…”
Section: Prace Poglądowementioning
confidence: 99%
“…In our study, the RNAseP gene was co-amplified with the AHI1 gene and served as an internal standard (two copies present in a subject with or without increase in the AHI1 gene). The formula of 'intermediate' measurement from manufacturer's protocol (Applied Biosystems pre-design TaqMan copy number assays kit) and other studies was used to analyze the estimated copy number (16,17,18). It is equal to 2 !2 KDDC t and represents the transformation of the relative abundance of the gene of interest in a given sample (DDC t ) from the 'C t ' scale to copy number scale.…”
Section: Verification Of Copy Numbers By Qrt-pcrmentioning
confidence: 99%